Immune Activities of Polycationic Vectors for Gene Delivery - Zhao, Xiaotian; Li, Xiaoming; Zhao, Yi; Cheng, Yuan; Yang, Yunqi; Fang, Zhiwei; Xie, Yangmei; Liu, Yao; Chen, Yinghui; Ouyang, Yuanming; Yuan, Weien (Frontiers in Pharmacology, 2017)
Polycationic vectors are used widely in the field of gene delivery, while currently their immune activities in vivo are poorly understood. In this comprehensive review, we aim to present an overview of existing mechanisms of adverse immune responses induced by the polycation/gene complexes, which includes the polycations themselves, the gene sequences and the ROS produced by them. These causes can induce pro-inflammatory cytokines, hypersensitivity as well as the activation of toll-like receptors, and finally the immunostimulation occur. In addition, we introduce some different opinions and research results on the immunogenicity of classical polycations such as polylysine (PLL), polyethyleneimine (PEI), polyamidoamine dendrimers (PAMAM), chitosan and gelatin, most of which have immunogenicity and can induce immunoreactions in vivo. The methods now used to adjust their immunogenicity are shown in the final part of this review. Nowadays, there is still no accurate conclusion on immunogenicity of polycations, which confuses researchers seriously in in vivo test. We conclude that further research is needed in order to skillfully utilize or inhibit the immunogenicity of these polycationic vectors.